Adolescents’ experiences of fluctuating pain in musculoskeletal disorders: a qualitative systematic review and thematic synthesis - Sonia Khanom (BMC Musculoskeletal Disorders, 2020)
Abstract Background Adolescents with chronic musculoskeletal pain experience daily fluctuations in pain. Although not all fluctuations are bothersome, pain flares are a distinct type of symptom fluctuation with greater impact. Since literature on the experience of pain flares is non-existent, the aim of this review was to (i) synthesise the qualitative literature on adolescents’ experiences of fluctuating pain in musculoskeletal disorders in order to (ii) identify knowledge gaps to inform future research on pain flares. Methods Electronic databases (CINAHL, MEDLINE, EMBASE, PsycINFO), grey literature and reference lists were searched from inception to June 2018 for qualitative studies reporting adolescents’ experiences of pain. Comprehensiveness of reporting was assessed using the Consolidated Criteria for Reporting Qualitative Health Research. Studies were analysed using thematic synthesis. Results Of the 3787 records identified, 32 studies (n = 536) were included. Principal findings were synthesised under three key themes: 1) symptom experience, 2) disruption and loss, and 3) regaining control. The first theme (symptom experience) describes adolescent’s perception and interpretation of pain fluctuations. The second theme (disruption and loss) describes the physical, social and emotional constraints faced as a result of changes in pain. The third theme (regaining control) describes coping strategies used to resist and accommodate unpredictable phases of pain. Each theme was experienced differently depending on adolescents’ characteristics such as their developmental status, pain condition, and the duration of the pain experience. Conclusions Adolescents with chronic musculoskeletal pain live with a daily background level of symptoms which frequently fluctuate and are associated with functional and emotional difficulties. It was not clear whether these symptoms and challenges were experienced as part of ‘typical’ fluctuations in pain, or whether they reflect symptom exacerbations classified as ‘flares’. Further research is needed to explore the frequency and characteristics of pain flares, and how they differ from their typical fluctuations in pain. The review also highlights areas relating to the pain experience, symptom management and health service provision that require further exploration to support more personalised, tailored care for adolescents with chronic musculoskeletal pain.